The Role of Seaweed in Carbon Sequestration and Climate Change Mitigation: A Review of Blue Carbon Potential - Mulyani, Sri (PT FORMOSA CENDEKIA GLOBAL, 2026)
Seaweed farming has emerged as a viable solution for mitigating climate change by sequestering carbon through blue carbon processes. This review examines the carbon sequestration potential of seaweed by focusing on the environmental factors influencing growth, the effectiveness of various farming methods, and the role of seaweed within broader climate mitigation strategies. The review consolidates findings from multiple studies, highlighting species such as Kappaphycus alvarezii, Ulva lactuca, and Gracilaria spp., which exhibit varying growth rates and carbon capture capacities. Key environmental conditions, including temperature, salinity, nutrient availability, and CO₂ levels, are shown to significantly influence the carbon sequestration potential of seaweed farming. The integration of seaweed farming into sustainable aquaculture systems, such as Integrated Multi-Trophic Aquaculture (IMTA), is identified as an effective strategy for enhancing nutrient cycling and improving carbon storage. While seaweed farming offers substantial potential, challenges such as regulatory barriers, environmental risks, and infrastructure limitations must be addressed to enable large-scale adoption. The review calls for further research to refine methodologies, optimize farming practices, and examine the socio-economic dimensions of seaweed farming, thereby ensuring its viability as a long-term climate change mitigation solution.